2008
DOI: 10.1016/j.neuroimage.2008.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Touch, sound and vision in human superior temporal sulcus

Abstract: Human superior temporal sulcus (STS) is thought to be a key brain area for multisensory integration. Many neuroimaging studies have reported integration of auditory and visual information in STS but less is known about the role of STS in integrating other sensory modalities. In macaque STS, the superior temporal polysensory area (STP) responds to somatosensory, auditory and visual stimulation. To determine if human STS contains a similar area, we measured brain responses to vibrotactile somatosensory, auditory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
147
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 174 publications
(160 citation statements)
references
References 65 publications
8
147
0
1
Order By: Relevance
“…Multisensory zones are frequently located on such borders between unisensory cortices (Wallace et al, 2004;Beauchamp et al, 2008). Interactions between auditory and somatosensory modalities in the perisylvian region have been suggested by imaging studies showing overlapping responses to sound and touch in this region (Foxe et al, 2002;Ozcan et al, 2005;Schurmann et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multisensory zones are frequently located on such borders between unisensory cortices (Wallace et al, 2004;Beauchamp et al, 2008). Interactions between auditory and somatosensory modalities in the perisylvian region have been suggested by imaging studies showing overlapping responses to sound and touch in this region (Foxe et al, 2002;Ozcan et al, 2005;Schurmann et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…3A). The somatosensory stimuli were delivered using piezoelectric benders attached with elastic bandages (Beauchamp et al, , 2008. When activated, the benders (67 mm ϫ 32 mm) produced an intense vibrotactile percept similar to that of holding a vibrating pager or cell phone, without any accompanying auditory stimulation.…”
Section: Methodsmentioning
confidence: 99%
“…The upper bank of the superior temporal sulcus (uSTS) is one of the regions in the primate brain frequently implicated in integrating sensory information across modalities (Jones and Powell, 1970;Calvert, 2001;Ghazanfar and Schroeder, 2006;Beauchamp et al, 2008). The uSTS contains an anatomically defined multisensory region, the so-called temporal polysensory area, that receives sensory-related inputs from visual, auditory, and somatosensory cortices (Seltzer and Pandya, 1989;Barnes and Pandya, 1992;Padberg et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…It suggests a short-term acquisition of a new motor pattern related to the typewriting task. Previous studies reported this region as a multisensory integration center 15 . despite the sensorimotor features of the task, in the training early phase the subjects possibly used secondary cues such as, the visual information from typewrite (e.g., letters on the paper) and the sound emitted by pressing of each key.…”
Section: Changes In Alpha Asymmetry (8-12 Hz)mentioning
confidence: 89%